2016
DOI: 10.1093/ofid/ofw118
|View full text |Cite
|
Sign up to set email alerts
|

Continued Elevation of Interleukin-18 and Interferon-γ After Initiation of Antiretroviral Therapy and Clinical Failure in a Diverse Multicountry Human Immunodeficiency Virus Cohort

Abstract: Background. We assessed immune activation after antiretroviral therapy (ART) initiation to understand clinical failure in diverse settings.Methods. We performed a case-control study in ACTG Prospective Evaluation of Antiretrovirals in Resource-Limited Settings (PEARLS). Cases were defined as incident World Health Organization Stage 3 or 4 human immunodeficiency virus (HIV) disease or death, analyzed from ART weeks 24 (ART24) to 96. Controls were randomly selected. Interleukin (IL)-6, interferon (IFN)-γ-inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…We found that elevated IL-18 levels at week 4 post-ART were associated with early mortality. This is consistent with a recent study demonstrating that persistently high levels of IL-18 are associated with clinical failure despite ART initiation in HIV-infected patients (20% of whom also had active TB) [ 35 ]. Notably, the NLRP3 rs10754558-G allele was also linked to elevated IL-18 levels at week 4 post–ART initiation in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…We found that elevated IL-18 levels at week 4 post-ART were associated with early mortality. This is consistent with a recent study demonstrating that persistently high levels of IL-18 are associated with clinical failure despite ART initiation in HIV-infected patients (20% of whom also had active TB) [ 35 ]. Notably, the NLRP3 rs10754558-G allele was also linked to elevated IL-18 levels at week 4 post–ART initiation in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…It is interesting to compare our results to a recent multi-national study by [ 12 ] that examined plasma concentrations of IFN-γ in a cohort of treatment-naïve HIV-positive subjects in low- and middle-income countries before and after ART therapy [ 12 ]. In that study, subjects with higher VL and lower CD4 count at baseline were more likely to have persistent elevation of IFN-γ after 24 weeks of ART therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cross-sectional nature of our study, we were unable to evaluate the temporal relationship between the nil QFT value and ART use or clinical outcomes. The two studies are also difficult to directly compare given differences in subject demographics and the lack of an HIV-negative control group in the study by Balagopal et al However, their study suggests that persistently elevated IFN-γ levels in patients on ART may portend better long-term clinical outcomes in the setting studied by [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This chronic state of inflammation/immune activation, that it is established during HIV-infection as a result of the complex interactions between viral and host factors, may be associated to clinical consequences despite of efficient cART. Increased values of IL-18 have been associated with clinical cART failure in HIV-infected patients [ 35 ] and high level of IL-8 has been associated with lower number of CD4 + cell count and HIV disease progression in children [ 36 ]. Patients of group B in our study, who did not recover from anemia, had indeed higher levels of IL-8 and IL-18.…”
Section: Discussionmentioning
confidence: 99%